Model Pemgembangan Mutu Pendidikan Dalam Perspektif Philip. B. Crosby - Marita Lailia Rahman (Institut Agama Islam Tribakti Kediri, 2020)
Some figures present the concept of quality to the world’s corporate which then many scientists have adopted for the education’s world. The famous Deming’s quality concept is plan, do, check, analyze, while the famous Juran’s quality concept is quality planning, quality controlling, and quality improvement. All these concepts if applicable in the world of education will have a positive impact on the improvement of quality’s education. Some figures as Philip Crosby offer some strategies to increase quality. It can be adopted for educational institution to improve its quality. Crosby offer Zero Defect concept that explained for fourteen steps to applicate in every educational institution in order to manage and improve education’s quality. Every manager or the leader of educational institution should always innovate and develop their educational institutions so that students can compete in the era of globalization [Beberapa tokoh menyajikan konsep mutu untuk dunia perusahaan yang kemudian banyak para ilmuwan yang mengadopsinya untuk dunia pendidikan. Konsep mutu Deming yang terkenal adalah plan, do, check, analyze. Sedangkan konsep mutu Juran yang terkenal adalah trilogi Juran yaitu perencanaan kualitas, pengendalian kualitas, dan perbaikan kualitas. Semua konsep tersebut jika dapat diterapkan dalam dunia pendidikan akan memiliki dampak positif bagi peningkatan mutu pendidikan. Para tokoh seperti Philip Crosby pun menawarkan beberapa strategi untuk meningkatkan mutu. Hal tersebut dapat diadopsi bagi lembaga pendidikan untuk meningkatkan kualitasnya. Crosby menawarkan konsep Zero Defect yang dijabarkan lagi dalam empat belas langkah untuk diaplikasikan dalam setiap organisasi ataupun lembaga pendidikan agar dapat mengatur dan meningkatkan mutu lembaga pendidikan. Setiap manajer atau pimpinan lembaga pendidikan seharusnya selalu berinovasi dan mengembangkan lembaga pendidikannya agar peserta didik dapat bersaing di era globalisasi.]